A Ku-Band Foldable Reflectarray Based on a Maltese-Cross Microstrip Element - S. V. Polenga; R. O. Ryazantsev; A. D. Poligina; R. M. Krylov; E. A. Litinskaya; Yu. P. Salomatov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Reflectarrays have a number of design and functional advantages over their closest analogue - reflector antennas (RA). Although microstrip elements are the most preferred reflectarray elements, single-layer microstrip elements do not allow accurate phase control due to the limited phase adjustment range and a high phase slope. The use of multilayer elements significantly complicates the antenna design and increases its cost. The development of a single-layer element that allows more than 360° phase adjustment and a low phase curve slope is urgent.Aim. To develop a single-layer microstrip phase-correcting element with a phase adjustment range of more than 360° and to design a reflectarray on its basis for operation in satellite communication networks.Materials and methods. Numerical studies were carried out using finite element analysis and the finite-difference time-domain method. Radiation patterns were measured using the near-field scanning method in an anechoic chamber.Results. A phase-correcting element based on a single-layer Maltese cross-shaped microstrip element with close to linear dependence of element size on the phase of the reradiated wave and more than 360° phase adjustment range was developed. On the basis of the investigated element, a foldable reflectarray was designed. The reflector consists of four subarrays, which provide its compact folding for transportation. The results of experimental studies confirmed a high efficiency of the reflectarray, the gain of which is 1.5 dB lower than that of an identical overall dimensions RA in a 7 % operating frequency band. The operating frequency band of the reflectarray in 1 dB gain zone was 11 %.Conclusion. On the basis of a Maltese cross microstrip element, it is possible to implement a single-layer reflectarray with a more than 10 % frequency band. The developed prototype showed the possibility of creating highly efficient foldable reflectarrays for operation in satellite communication and television terminals.